Do Corporate Codes of Ethics Reflect National Character? Evidence from Europe and the United States - Langlois, Catherine C.; Schlegelmilch, Bodo B. (Journal of International Business Studies, 1990)
This paper analyses the usage and contents of corporate codes of ethics. The results from a sample of 600 large European companies are contrasted with findings reported for similar U.S. firms. The comparison reveals that significantly fewer European than U.S. firms adopted codes of ethics. In Europe, the large majority of codes have been introduced only very recently and there are indications that codes made their way into Europe via subsidiaries of U.S. firms. However, there are striking differences in content between U.S. and European codes of ethics pointing to the existence of a distinctly European approach to codifying ethics.